Comparative study of origin of the cosmos in Islam and Christianity in the light of modern science - Amafua, Mahfuth Khamis (International Institute of Islamic Thought and Civilizations (ISTAC), International Islamic University Malaysia, 2012)
This dissertation discusses the origin and formation of cosmos in Islam and Christianity in the light of modern science. The motive behind this research has been to find out areas of disagreement as well as the common ground where the three parties (Islam, Christianity and modern science) could integrate and utilize each other's for prosperity and enhancement of human community or the entire world. The study argues that there is no doubt that the three parties have provided indisputable and remarkable accounts regarding the origin and formation of the cosmos that has shaped the worldview and attitude of mankind through and through. However, the findings of this study reveal that the explanations given by the modern science are limited as compared to the comprehensive explanations provided by theology that entails metaphysics, ontology, the knowledge concerning the unseen world, as well as that of eschatology and the like. As we have seen, modern science has failed in one way or the other to provide us with information to the origin of the cosmos as well as the origin of man, the fate of the universe, including the purpose of our existence in this world and of course our final destination. Furthermore, it (modern science) could not provide a code of ethics or moral guidelines for human beings to rightfully govern themselves and sustainable environment in order to pave the way to a bright future for generations to come. It then follows that there exists a dire necessity and urgency for the reunification of science with religion. Since modern science is not compatible with Christianity, Islam can easily supply the required religious background to modern science and bring the cosmic truth espoused by religions through scientific scrutiny.